The Inflammatory Exposome of Major Depressive Disorder in an Egyptian Sample - deif, reem (AUC Knowledge Fountain, 2024)
Major depressive disorder (MDD) has been recognized as a global public health concern affect-ing the lives of 264 million people with increasing prevalence worldwide. Inspired by the expo-somic research, this study aims to investigate the dynamic and complex interplay between dif-ferent demographic, lifestyle, environmental factors and bimolecular factors that are potentially involved in the pathology of MDD in a sample of Egyptian adults living in Cairo. This is in an attempt to acknowledge the biological underpinnings of MDD without underestimating the role of environmental influences. The context of Egypt provides richness to the current study given the national transition from an agricultural society, to a more industrialized one. The sample in-cluded 107 adults from both genders between the ages of 18 and 50. Convenience sampling was used to recruit participants from different social and community platforms. Participants were excluded on the basis of having comorbid psychotic or neurodegenerative disorders, terminal conditions and cognitive disabilities that might interfere with their clinical presentation. A com-prehensive questionnaire was developed and then refined to collect demographic, psychosocial, lifestyle and environmental data in addition to a mini mental state examination (MMSE). Addi-tionally, the Arabic version of the Beck Depression Inventory-II (BDI-II) was used to assess the severity of depressive symptoms and to generate a symptoms profile. The translated Mini In-ternational Neuropsychiatric Interview (MINI 7.0.2) was used to diagnostically differentiate be-tween participants with MDD and healthy controls in addition to identifying cases of past episodes and recurrent episodes of MDD. Participants were also required to give blood samples for the examination of a wide range of biomarkers that are theoretically expected to be linked with MDD. These included EGF, FGF-2, FGF-9, FGF-21, FGF-22, IFN-γ, IGF-1, IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-17, TNF-α , VEGFC, and VEGFD in addition to complete blood parameters. Statistical analysis were conducted including basic descriptive testing, correlational testing and mediation analysis. Results show several significant correlations between different inflammato-ry and neurotrophic biomarkers. Significant correlations were also established between different lifestyle factors and MDD outcomes and different biomarkers and MDD outcomes. Some bio-markers (namely, EGF, FGF-2, FGF-21, FGF-9, IGF-1, IL-1β, IL-17, IL-6, TNF-α , VEGFD, WBC, MCH and RBC) showed symptom-specific correlations. More in-depth analysis revealed the mediational effect of a few biomarkers between some risk factors and MDD outcomes. Howev-er, some challenges limit the generalizability of the findings including the sample size, the cross-sectional study design and the use of peripheral rather than central biomarkers. In conclusion and despite its limitations, this study offers valuable insights about the complexity of MDD in an Egyptian sample combining psychosocial, environmental and biomolecular data. Such find-ings highlight the pressing need for a more personalized approach in the study of MDD and other psychiatric disorders. It shows real potential of investing in precision mental health re-search for the development and enhancement of personalized intervention and prevention strategies.